Aggregation with XMLSPY the advantages of XML...without all the angle brackets. - Solymosi, Andrew (XML journal :the ultimate enterprise resource.)
Aggregation in XML is not trivial. Altova's XMLSPY offers a number of features facilitating this process. This article presents an example, including best practices and practical programming techniques-especially useful for those who don't like typing a lot of angle brackets.